REGION (AREA) AS TOURISTIC PRODUCT (Research Bulletins of the Faculty of Economic Sciences, 2021)
Article shows concepts of perception of regions as touristic products. The present thesis may prove useful for local governments in Poland which undertake various activi-ties for the development of the tourist function, e.g. when formulating a development strategy or a promotional campaign. Apart from it, the thesis constitutes an important source of information for students of specialties connected with tourism.
Keywords: touristic product, area of touristic reception, touristic region